Response of the Ionospheric TEC to SSW and Associated Geomagnetic Storm Over the American Low Latitudinal Sector - J. B. Fashae; O. S. Bolaji; A. B. Rabiu (Space Weather)
Abstract During the sudden stratospheric warming (SSW) event in 2013, we investigated the American low latitude around 75°W. We used 12 Global Positioning System (GPS) receivers, a pair of magnetometers, and the NASA Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite airglow instrument to unveil the total electron content (TEC), inferred vertical drift, and the changes in the neutral composition, respectively. A major SSW characterized the 2013 SSW event with the main phase (7–27 January 2013) overlapped by a minor geomagnetic storm (17 January 2013). The late morning inferred downward‐directed E X B drift did not support the varying equatorial ionization anomaly (EIA) signature during the SSW onset (7 January 2013). The mid‐January (15–16 January 2013) witnessed enhancement in the varying inferred upward‐directed E X B drift at both hemispheres. On 17 January 2013, there were reductions in the varying inferred upward‐directed E X B drift at both hemispheres. Generally, the SSW effect on TEC around 15–16 January 2013 is more pronounced than the SSW onset. During the mid‐January (15–16 January 2013), the higher northern EIA crests are facilitated majorly by the SSW compared to the photo‐ionization that primarily enabled the southern crests. On 17 January 2013, the combined effect of photo‐ionization and SSW contribution was majorly responsible for the slight reduction in the northern crest. In the southern hemisphere, photo‐ionization played the lead role as the SSW, and the minor geomagnetic storm roles are secondary in enhancing the southern crest.